Global Aging and Economic Convergence: A Real Option or Still a Case of Science Fiction? - Hendrik P. van Dalen (Tinbergen Institute, 2007)
How does global aging affect the convergence in global economic development? Both the developing and developed world will be characterized for the coming decades by aging populations. Changes in the age distribution of a population are an important determinant of economic performance as they affect wealth accumulation and dependency burdens, yielding a demographic dividend of extra growth. During the twenty years from 1975 to 2005 Europe and the US have benefited from a strong demographic dividend. However, in the decades to come this effect will be reversed and the driving force behind the wealth of nations has to be sought elsewhere. Africa and, to some extent, India might benefit from the demographic dividend. However, this potential growth phase may well disappear if supporting conditions for growth are absent. Large-scale migration is not expected to be a sustainable solution to unbalanced global economic developments. Remittances, Foreign Direct Investment (FDI) and Official Development Assistance (ODA) will remain necessary capital flows for the developing world in the near future. Remittances offer no structural solution to reduction of poverty as these funds flow to a selective group of families and are allocated generally to consumption rather than to investment purposes. Migration of a temporary nature in conjunction with offshore outsourcing of services and production may offer a solution for the dilemmas of population and development, which OECD donors face in offering development assistance and designing immigration policy.
Keywords: E2; F22; F35; J11; N30; 330; aging; convergence; migration; remittances; population growth; Alternde Bevölkerung; Entwicklungskonvergenz; Entwicklungshilfe; Kapitalmobilität; Bevölkerungswachstum; Internationale Wanderung; Welt